Deep Learning-Based Islamic Religious Education to Foster Religious Values among Generation Z - Della Putri Aprillianti; Agus Fakhruddin; Mokh. Iman Firmansyah (Abjadia : International Journal of Education, 2026)
Generation Z is a dominant demographic group in Indonesia with unique characteristics as a generation highly exposed to globalization and digital technology. The phenomenon of moral degradation experienced by this generation is characterized by a weakening of social ethical values, increasing individualism, and negative behaviors such as bullying and a lack of respect for social norms. Islamic Religious Education (PAI) plays a crucial role as a bulwark in the formation of the religious and moral character of Generation Z. This article examines Islamic Religious Education (PAI) learning, including PAI teachers' strategies in fostering students' religious awareness through an adaptive and contextual in-depth learning approach. This study used a mixed method with a Concurrent Embedded design, namely a combination of quantitative and qualitative approaches through observation, questionnaires, teacher interviews, and analysis of PAI curriculum documents in a high school in Bandung City. The results show that the PAI learning strategy based on in-depth learning improves deep religious understanding, learning motivation, and internalization of positive religious values. This growing religious awareness contributes to strengthening students' moral character, discipline, sense of responsibility, and tolerance. Major obstacles, such as the negative influence of social media and low interest in learning, can be overcome with innovative methods and collaborative support from teachers, parents, and the community. These findings indicate that developing Islamic Religious Education (PAI) learning strategies that adapt to the psychosocial and cultural needs of Generation Z is crucial in addressing moral decline and preparing the nation's next generation with strong and religious characters.